Pengaruh penambahan surfaktan sodium lignosulfonat (SLS) dalam proses pengendapan nano calcium silicate (NCS) dari geothermal brine - M. Ridho Ulya; Indra Perdana; Panut Mulyono (Jurnal Rekayasa Proses, 2017)
High concentration of dissolved silica in geothermal brine frequently causes operational problem in production of steam for electric generation. Mitigation of silica scaling is necessary to reduce the risk of steam production failure. In the present work, silicic acid in Dieng geothermal brine was reduced by introduction of calcium hydroxide that lead to formation of insoluble nano calcium silicates (NCS).The purpose of this work was to control size of the precipitated NCS by introducing surfactant sodium lignosulfonate (SLS) as surfactant in the Ca(OH)2 added geothermal brine. The effect of temperature (30, 50 and 70°C), pH (7, 8 and 9), and surfactant concentration (0.05, 0.15 and 0.30% (w/v)) on the particle size of the resulting NCS was studied to obtain the optimum operating condition. The precipitation-sedimentation behavior of the resulting particles was measured in a vertical tube. Having measured the solid density and solution density and viscosity, average diameter of the precipitated particles was determined using stoke’s principle. The calculated particle size was the compared with measurement result using particle size analyzer (PSA). The soluble silica concentration in the solution was measured using spectroscopy method while composition of the resulting solid particles was measured using EDX and FTIR. Experimental results showed that the dissolve silica in Dieng geothermal brine can be reduced and controlled with the addition of Ca(OH)2 and surfactant SLS. The greater the concentration of surfactant SLS, the smaller the resulting particle size. It was found that the formation of NCS particles was accompanied with precipitation of silica and salts. The optimum condition of NCS formation was at temperature 30°C and pH 9 while the concentration of surfactant SLS added to the brine was 0.3 % (w/v).